Pedagogical Competency Development Program for Special Supervising Teachers for Slow Learner Children at SMPN 6 Jakarta - Susanti, Ayu; Aprilia, Imas Diana; Homdijah, Oom sitti (Angstrom Centre of Education, 2024)
The main philosophical foundation in implementing inclusive education in Indonesia is the Pancasila philosophy which has the motto